Blood Flow Restriction Training for Meniscus Repair Surgery - Yuki Yamanashi MD; Sachin Allahabadi MD; C. Benjamin Ma MD; Ivan Arriaga DPT (SAGE Publishing, 2024)
Background: Blood flow restriction (BFR) is a training tool that involves wearing a tourniquet or occlusive device during exercise. Data support that low-load training with BFR may produce muscle hypertrophy similar to standard high-load training. Because of the weight-bearing and range of motion (ROM) restrictions after meniscal repair, patients encounter substantial atrophy of lower extremity musculature. We perform BFR for these patients to limit atrophy postoperatively with the goal of facilitating their return to prior function and sports. Indications: We incorporate BFR in the postoperative rehabilitation protocol for patients undergoing meniscal repair not involving the root. Patients with the following are excluded: acute or severe cardiac disease, peripheral vascular disease, blood pressure over systolic 180 mm Hg or diastolic 100 mm Hg, hemophilia, thrombophlebitis or history of deep vein thrombosis, severe anemia, and sickle cell disease. Technique Description: An automated BFR device calculates the patient's limb occlusion pressure (LOP) and titrates to 50% to 80% of LOP for lower extremity exercises. Exercise parameters typically consist of 4 sets of each exercise, totaling 75 repetitions, with 30-second interset rest. Patients undergo a standard 3-phase postoperative rehabilitation protocol. Phase I (weeks 0-6): Patients are nonweightbearing, may be either footflat weightbearing or partial weightbearing at the surgeon's, with ROM restricted 0 to 90 in a hinge knee brace throughout the phase. Exercises include quadriceps sets with neuromuscular electrical stimulation and straight leg raises and short/long arcs quadriceps. Phase II (weeks 7-8): Patients progress to weightbearing and ROM as tolerated and begin exercises including double mini squats, hamstring curls, double leg press, and double leg heel raises. Phase III: (weeks 9+): Patients perform double and single leg bridges, double leg bridges on ball with knee band, squats, single leg press, and single leg heel raises, all with the goal of returning to sports. Results: Prior systematic review data demonstrate low-load training with BFR increases muscle strength and induces hypertrophy relative to low-load training alone. No significant differences for Knee Injury and Osteoarthritis Outcome Score (KOOS) subscales between BFR training group and control group. Discussion: BFR training may facilitate postoperative recovery in patients undergoing meniscal repair surgery by helping mitigate muscular atrophy. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.